Liquid Organic Fertilizer (LOF) as a Waste Processing Strategy to Support Increasing Crop Production: a Review: Pupuk Organik Cair (POC) sebagai Strategi Pengolahan Limbah dalam Mendukung Peningkatan Produksi Tanaman: sebuah Ulasan - Haryanta, Dwi; Widya, Surya Ari (Journal of Applied Plant Technology, 2024)
The study aims to compare various information discussions about LOF viewed from various needs so that complete information is presented, making it easier for practitioners to find information about LOF so that they can practice in many alternative choices, providing an overview of the variation and diversity of problems related to LOF including sources of raw materials, effects of LOF treatment on plants, application techniques and others. Information about LOF is taken from research papers or ideas published in reputable international journals to national journals that have not been accredited. Liquid organic fertilizer can be made from various types of waste such as rice washing water, banana stems, food scraps, market waste, kitchen waste, fish offal, water hyacinth, weed leaves, solid/liquid animal waste (buffalo, cow, goat, rabbit, chicken), shrimp, seaweed, sprouts, catfish waste and coffee grounds. LOF application by spraying or pouring on plants, dilution with a concentration of 1 ml - 60 ml per liter of solution. LOF application has a very real effect to no real effect on plant growth and yield. Liquid organic fertilizer as one of the organic waste processing products to support increased agricultural production.